Chronological events in the surgery of the septum - Munjal, Manish; Arora, Pankaj; Munjal, Shubham; Saggar, Tulika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Nasal obstruction unilateral or bilateral, secondary to congenital birth passage or adult, nasal trauma requires surgical intervention of the deviated septum. Intervention ranges from a minimal septal repositioning to submucosal resection, simple septoplasty or the extensive extracorporeal septoplasty. The development of septal surgery with the developments in the field of rhinology has been reviewed.